2019
DOI: 10.3390/w12010101
|View full text |Cite
|
Sign up to set email alerts
|

Using OCO-2 Satellite Data for Investigating the Variability of Atmospheric CO2 Concentration in Relationship with Precipitation, Relative Humidity, and Vegetation over Oman

Abstract: Recognition of the carbon dioxide (CO2) concentration variations over time is critical for tracing the future changes in climate both globally and regionally. In this study, a time series analysis of atmospheric CO2 concentration and its relationship with precipitation, relative humidity (RH), and vegetation is investigated over Oman. The daily XCO2 data from OCO-2 satellite was obtained from September 2014 to March 2019. The daily RH and precipitation data were also collected from the ground weather stations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The occurrence of the summer monsoons is a major source of precipitation and thus an important factor controlling the vegetation in these regions. Generally, March to May is treated as pre-monsoon, June to September as monsoon and October to November as post-monsoon in most of the Asian regions [63]. The CO 2 concentration is found to be maximum in the pre-monsoon and minimum in monsoon (Figure 6c,d).…”
Section: Monthly Averaged Time-series Comparisonmentioning
confidence: 96%
See 1 more Smart Citation
“…The occurrence of the summer monsoons is a major source of precipitation and thus an important factor controlling the vegetation in these regions. Generally, March to May is treated as pre-monsoon, June to September as monsoon and October to November as post-monsoon in most of the Asian regions [63]. The CO 2 concentration is found to be maximum in the pre-monsoon and minimum in monsoon (Figure 6c,d).…”
Section: Monthly Averaged Time-series Comparisonmentioning
confidence: 96%
“…The low wind speed during the pre-monsoon causes slight mixing in the boundary layer which also contributes in the CO2 concentration [66]. Moreover, a large Asia experiences a monsoon climate, which plays a significant role in the CO 2 concentrations [63]. Asian monsoon may be further classified into the Southwest Monsoon and the East Asian Monsoon [64].…”
Section: Monthly Averaged Time-series Comparisonmentioning
confidence: 99%
“…To minimize the differences between the spatial and temporal resolutions of the different orbital sensors used in this study, the process described in Figure 5 was employed, which establishes a standard in the acquisition of data from the coordinates obtained in the OCO-2 platform. We emphasize that several studies have been conducted using different time and spatial scales [6,7,27].…”
Section: Study Regionmentioning
confidence: 99%
“…Several studies con rm that photosynthesis is the main regulator of atmospheric carbon sinks [10,24,25,26]. However, photosynthesis is a process sensitive to climatic variations such as relative humidity [27], precipitation [28], evapotranspiration [29], and incident solar irradiance [30].…”
Section: Introductionmentioning
confidence: 99%
“…51 On the other hand, a study in India and Oman showed that CO 2 concentration decreased during rainy seasons as it also allowed vegetation growth that took up CO 2. 52,53 This may be the reason for the negative correlation of CO 2 , malaria incidence, and NTD in the Philippines as malaria, dengue fever, and leptospirosis are common diseases during the rainy season. 29 In addition, schistosomiasis was also found to be influenced by rainfalls and flooding by which the latter can "facilitate human-parasite contact".…”
Section: Correlation Of Global Co 2 Levels With Health Factorsmentioning
confidence: 99%